Cops in crisis?: ethnographic insights on a new era of politicization, activism, accountability, and change in transatlantic policing - Deuchar, Ross (Policing and society, 2020)
Against the complex backdrop of a post-modern era, characterised by a renewed emphasis on public accountability, oppositional social and political movements, it has been argued that traditional agents of social control have increasingly begun to experience a sense of disempowerment. Nowhere has this been more apparent than within the context of policing, where the increased influence of the mass media, social media, and newly empowered groups has led to an apparent legitimacy crisis on both sides of the Atlantic. To better understand officers’ views, attitudes, and perspectives about the changing landscape of policing, this paper reports on insights from a comparative study involving participant observation in two counties in a Southern State in the United States of America and three inner-city areas in Scotland. The observations were paired with in-depth semi-structured interviews with 18 American and 22 Scottish officers. The data suggest that officers on both sides of the Atlantic are hostile towards the increasing influence of new forms of media and digital activism. Many officers also expressed concern for declining public cooperation and perceived there to have been a general diminution of police authority and enforcement tactics. Finally, there was a general feeling of reduced officer self-legitimacy among the participants but an increased awareness of procedural justice and alternative (and more covert) enforcement strategies. The implications from these findings are discussed in terms of changing perceptions of justice, legitimacy, social ideology, and the proposed consequences for rights-based policing in the 21st Century.